2005
DOI: 10.1021/ac051329b
|View full text |Cite
|
Sign up to set email alerts
|

Desorption/Ionization Fluence Thresholds and Improved Mass Spectral Consistency Measured Using a Flattop Laser Profile in the Bioaerosol Mass Spectrometry of Single Bacillus Endospores

Abstract: Bioaerosol mass spectrometry (BAMS) is being developed to analyze and identify biological aerosols in real-time. Mass spectra of individual Bacillus endospores were measured here with a bipolar aerosol time-of-flight mass spectrometer in which molecular desorption and ionization were produced using a single laser pulse from a Q-switched, frequency-quadrupled Nd:YAG laser that was modified to have an approximately flattop profile. The flattened laser profile allowed the minimum fluence required to desorb and io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 41 publications
(73 reference statements)
4
54
0
Order By: Relevance
“…This is prudent given the goal of high sensitivity and extended mass range. The authors have investigated laser fluence in various contexts before [13,41], so it is discussed only briefly here and grouped with a description of observed ion peaks. More substantial examinations of the other parameters follow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is prudent given the goal of high sensitivity and extended mass range. The authors have investigated laser fluence in various contexts before [13,41], so it is discussed only briefly here and grouped with a description of observed ion peaks. More substantial examinations of the other parameters follow.…”
Section: Resultsmentioning
confidence: 99%
“…A particle's velocity combined with the exact time it passes through the last scattering laser provide the necessary timing to appropriately fire a 355 nm Nd:YAG desorption/ionization (DI) laser (Big Sky Laser Technologies, Inc. Ultra, Bozeman, MT) as the particle reaches the center of the mass spectrometer ion source. The DI laser, which is aligned perpendicular to both the particle beam and the axis of the spectrometers, produces 7 ns pulses that are flattopped and focused to a spot size of 380 m [41]. Delayed extraction is then used to simultaneously accelerate both positive and negative ions into the opposing linear time-of-flight mass spectrometers, each configured with ion guiding capabilities and identically biased, MCP-based detectors.…”
Section: Instrumentationmentioning
confidence: 99%
“…The desorption/ionisation laser used by the ATOFMS also complicates quantitative speciation. Shot-to-shot fluctuations in laser output power and variations in power density (Gaussian) across the laser beam (Steele et al, 2005;Wenzel and Prather, 2004) create variance in the amount of a particle that is desorbed and can also lead to variations in resultant mass spectral peak height and area (Reinard and Johnston, 2008).…”
Section: Atofms Data Analysismentioning
confidence: 99%
“…Variation also exists in the energy present in the laser beam. Previous research has shown that the optics used in focusing the D/I laser create a laser profile that has a roughly "flat top" distribution of energy as described in Chapter Two; 64 however particles that are focused near the edges of the beam may experience a lower D/I energy. 67 Also, the laser fluence of 0.70 nJ/µm 2 is an average value of 50 consecutive laser pulses, so variation exists shotto-shot, although it is typically less than 5%.…”
Section: Signal Reproducibility Of Spamsmentioning
confidence: 99%
“…SPAMS at LLNL was previously known as Bioaerosol Mass Spectrometry (BAMS) and has been applied to the detection of various species of Bacillus spores, [64][65][66][67][68][69][70] viruses, 64 toxin simulants, 64 fungi, 66 and Mycobacteria, 70 with and without the use of a chemical matrix to aid in ionization. Matrix-free systems are ideal for real-time and online detection systems, as no sample preparation and thus very few reagents are needed for the analysis.…”
mentioning
confidence: 99%